The NLR Protein Encoded by the Resistance Gene Ty-2 Is Triggered by the Replication-Associated Protein Rep/C1 of Tomato Yellow Leaf Curl Virus - Shen, Xuexue; Yan, Zhe; Wang, Xiaoxuan; Wang, Yinlei; Arens, Marjon; Du, Yongchen; Visser, Richard G. F.; Kormelink, Richard; Bai, Yuling; Wolters, Anne-Marie A. (Frontiers in Plant Science, 2020)
The whitefly-transmitted tomato yellow leaf curl virus (TYLCV) is one of the most destructive viral pathogens of cultivated tomato. To combat TYLCV, resistance gene Ty-2 has been introduced into cultivated tomato (Solanum lycopersicum) from wild tomato species Solanum habrochaites by interspecific crossing. Introgression lines with Ty-2 contain a large inversion compared with S. lycopersicum, which causes severe suppression of recombination and has hampered the cloning of Ty-2 so far. Here, we report the fine-mapping and cloning of Ty-2 using crosses between a Ty-2 introgression line and several susceptible S. habrochaites accessions. Ty-2 was shown to encode a nucleotide-binding leucine-rich repeat (NLR) protein. For breeding purposes, a highly specific DNA marker tightly linked to the Ty-2 gene was developed permitting marker-assisted selection. The resistance mediated by Ty-2 was effective against the Israel strain of TYLCV (TYLCV-IL) and tomato yellow leaf curl virus-[China : Shanghai2] (TYLCV-[CN : SH2]), but not against tomato yellow leaf curl Sardinia virus (TYLCSV) and leafhopper-transmitted beet curly top virus (BCTV). By co-infiltration experiments we showed that transient expression of the Rep/C1 protein of TYLCV, but not of TYLCSV triggered a hypersensitive response (HR) in Nicotiana benthamiana plants co-expressing the Ty-2 gene. Our results indicate that the Rep/C1 gene of TYLCV-IL presents the avirulence determinant of Ty-2-mediated resistance.